Revision of the genera Habetia Kirby, 1906 and Parahabetia gen. nov. from New Guinea (Orthoptera, Tettigoniidae, Conocephalinae, Agraeciini) - Ingrisch, Sigfrid (Zootaxa, 2021)
The genus Habetia Kirby, 1906 previously known from only four species or subspecies is revised based on unidentified specimens found in museum collections. H. multispinulosa Griffini, 1908 is given full species status, while H. pictifrons Karny, 1911 is removed from Habetia based on male and female characters and becomes the type species of the new genus Parahabetia gen. nov. Sixteen new species are described in Habetia, and one new species and two new subspecies in Parahabetia. The most significant characters for the differentiation of species of Habetia are male tenth abdominal tergite, cerci, subgenital plate, and male internal genitalia with the titillators that basically form a pair of roughly U-shaped sclerites that vary between species from simple, curved sclerites to modified structures with additional sclerotized branches and the sclerites can be connected with septa to form complex shapes. In contrast, males of Parahabetia have elongate titillators provided at end with a crest. In the larger species of Habetia the stridulatory file on the underside of the male left tegmen has a step in pre-apical area that is missing in the smaller species; one species with a weak step is intermediate between both groups. Unique modifications of single species in Habetia are an apical dorsal extension of the male subgenital plate in H. imitatrix Karny, 1912 and a hardened phallus sheath between phallus and subgenital plate in H. tuta sp. nov. Females of Habetia have straight ovipositors that vary in length and in the shape of the dorsal margin between species. Females can also be differentiated by species specific modifications of the subgenital plate. In Parahabetia the ovipositor is rather short and curved similar to the condition in the genus Philmontis Willemse, 1966 but has the apical area slightly recurved. Keys to the species of both genera are provided. Habetia species have been found throughout New Guinea except so far for Papua Barat; although they were mainly found in the North and the East. Parahabetia species are currently only known from the East of New Guinea. The following species and subspecies are described as new: Habetia bivittata sp. nov., H. curvata sp. nov., H. dentata sp. nov., H. elevata sp. nov., H. kondiu sp. nov., H. lalibu sp. nov., H. nigricauda sp. nov., H. pallida sp. nov., H. pedala sp. nov., H. pilleata sp. nov., H. pinnigera sp. nov., H. quatrispina sp. nov., H. simbai sp. nov., H. sororcula sp. nov., H. tuta sp. nov., H. wau sp. nov., Parahabetia bispinosa sp. nov., P. pictifrons obtusa ssp. nov., P. pictifrons acuta ssp. nov.